Outage probability and ergodic capacity analysis in power splitting based full-duplex relaying networks of double rayleigh fading channel for vehicular communications - Phu Tran Tin; Duy-Hung Ha; Q. S. Vu; Tran Thanh Trang (Institute of Advanced Engineering and Science, 2020)
In this research, we present and investigate the system performance analysis in terms of the outage probability (OP) and ergodic capacity (EC) of the Full-duplex (FD) relaying networks via double Rayleigh fading channel. In this system model, we propose the power splitting (PS) protocol for the vehicular communications network. Firstly, we analyze and derive the integral form of the system OP and EC. Then, the correctness of the OP and EC expressions are verified by the Monte Carlo simulation. Finally, we can see that the analytical and the simulation results are matched with each other in the connection with the main system parameter.